Occupational Hazards for Workers in The Battery Factories and Phosphate Fertilizers: Brief Review and Case Presentation - Hattab, Faiez (The Indonesian Journal of Community and Occupational Medicine, 2023)
Background: Workers in the battery factory and phosphate fertilizer industry are exposed to harmful sulfuric acid and metal vapors in manufacturing units. Aims: To describe dental, oral, and general health hazards to underappreciated workers in these industries and factors associated with the occurrence and severity. Methods: Dental and oral conditions of workers in the production lines were determined by using indices for teeth erosion, oral hygiene, and gingival health. Interviews and questionnaires were used to assess the general health problems, habits, oral hygiene practices, years of service, protective and safety measures, etc. Results: Results: Surveys show that 67%–86% of production line workers experience symptoms of tooth sensitivity, dry mouth and nose, dysgeusia, burning/itchy eyes, and abdominal discomfort. They also complain of loss of appetite, fatigue, irritability, and muscle or joint pain. Examinations revealed that nearly all workers had poor hygiene and periodontal problems, with 78% experiencing gum bleeding on probing (33%) and spontaneous bleeding (45%). More than two-thirds (79%) of workers had dental erosion on anterior teeth and occlusal abrasion of the posterior teeth. A dense teeth discoloration on the eroded anterior and tartar deposits was obvious. Conclusions: Overexposure to hazardous vapors generated in the manufacturing processes associated with the unsafe workplace, lack of self-protection, poor personal health care, and inadequate medical services are factors strongly involved in the deterioration of workers’ health.